In-situ reaction of Ti-Si-C composite powder and formation mechanism of laser deposited Ti6Al4V/ (TiC+Ti3SiC2) system functionally graded material. (5th December 2019) - Li, Neng; Liu, Wei; Xiong, Huaping; Qin, Renyao; Huang, Shuai; Zhang, Guohui; Gao, Chao
Abstract: Ti-Si-C composite powder was designed as raw material for laser deposition, and fabricated into quasi-spherical powder particles. On this basis, Ti6Al4V/(TiC+Ti3 SiC2 ) system functionally graded material (FGM) was designed and fabricated using pure Ti powder and the fabricated Ti-Si-C composite powder. The microstructures of the gradient layers were analyzed by a scanning electron microscope (SEM) equipped with an X-ray energy dispersive spectrometer (EDS). An X-ray diffraction (XRD) spectrometer and a transmission electron microscope (TEM) were used for determination of the reaction products in the gradient layers. In-situ chemical reactions took place between elements Ti, Si and C in the deposited layers, and the reaction products included TiC and Ti3 SiC2 ceramics as well as Ti5 Si3 compound. Finally, Ti6Al4V/(TiC+Ti3 SiC2 ) system FGM with a planar size of 25 mm × 50 mm was fabricated and the total thickness of all the graded layers was 2.2 mm. The average three-point bending strength of the overall Ti6Al4V/(TiC+Ti3 SiC2 ) system FGM was high up to 995 MPa at room temperature, and the outermost layer exhibited the microhardness of 647.5 HV. Graphical abstract: Unlabelled Image Highlights: Composite powder method was proposed and Ti-Si-C composite powder was fabricated into quasi-spherical particles. Ti6Al4V/(TiC+Ti3 SiC2 ) system FGM was laser deposited using composite Ti-Si-C powder and Ti powder; In-situ reactions occurred between Ti, Si and C, with the products of TiC, Ti5 Si3 and Ti3 SiC2 ; Planar size of FGM was 25mm×50mm without cracks, and ductile ceramic Ti3 SiC2 was important in good forming; Average bend strength of FGM was high up to 995MPa.